Household resilience and coping strategies to food insecurity: An empirical analysis from Tajikistan - Bekhzod Egamberdiev; Ihtiyor Bobojonov; Lena Kuhn; Thomas Glauben; Kamiljon Akramov (Applied Economic Perspectives and Policy, 2024)
By applying Resilience Index Measurement Analysis to data from Tajikistan, this paper measures food insecurity resilience capacity. Another objective of this paper is to construct and integrate coping strategies into resilience discussions. The final objective is to analyze the role of resilience capacity and coping strategy in food security with an Instrumental Variable approach. Our results generally confirm that resilience and coping strategies increase food security, determined by food expenditure, household adequacy of fruit and vegetable consumption, and household food expenditure share. Moreover, resilience capacity has a moderating role in mitigating negative impacts of shocks on food security.
Keywords: D10; Q18; O53; 330; coping strategy; food security; instrumental variable; latent profile analysis; resilience capacity index